Distribution patterns of microplastics in subtidal sediments from the Sado river estuary and the Arrábida marine park, Portugal - Rodrigues, Diana; Antunes, Joana; Pais, Joana; Pequeno, João; Caetano, Paulo Sá; Rocha, Fernando; Sobral, Paula; Costa, Maria Helena (Frontiers in Environmental Science, 2022)
Understanding local accumulation patterns of microplastics (MPs) in subtidal sediments is crucial to assess how available such particles are for ingestion by benthic feeders and to identify the potential pollution sources in the region upon which is urgent to act. The coastal urban centers of Setúbal and Sesimbra (Portugal) and the multiple activities taking place at the contiguous Sado estuary and in the sheltered waters of Professor Luiz Saldanha Marine Park make this a relevant case study about MPs pollution in the seabed. Here, a short-term investigation assessed the spatiotemporal distribution, abundance, and composition of MPs on the nearshore seabed. Sediment samples were monthly collected from summer 2018 to winter 2019, in six stations. Despite the differences observed in rainfall between campaigns, no distinct patterns were detected in the accumulation of MPs throughout the sampled months. Yet, strong variations occurred among stations. The abundance of MPs in the Sado estuary (1042.8 ± 430.8 items kg −1) was higher in comparison to all the stations located along the marine park (52.9 ± 31.9 items kg −1). Fragments comprised 70% of particles found in estuarine sediments, while fibers were the predominant type in marine sediments. The majority of MPs collected in the estuary shared the same size class as the best represented grain size fraction: 0.250-0.500 mm. On average, the ratio between the abundance of MPs and the abundance of meiofauna organisms was higher in the estuary, suggesting more encounter rates, by both meiofauna and their predators, with MPs. The distribution of MP throughout the study area was moderately correlated with sediment sorting and organic matter content. Also, the distinct mineralogical content of each station indicates a reduced sediment transit between stations and consequently a weak MPs exportation from the estuary. The majority of the polymers identified by Fourier Transform Infrared Spectroscopy was denser than seawater. Polyethylene terephthalate (PET) represented 41% of the items analyzed and was mostly assigned to fibers and fiber bundles. Unveiling the distribution patterns of MPs along this segment of the Portuguese west coast enabled to identify the high-risk areas where the implementation of preventive measures is urgent.